Mesoscale and Submesoscale Processes in the Southeast Atlantic and Their Impact on the Regional Thermohaline Structure. Issue 3 (12th March 2018) - Capuano, Tonia Astrid; Speich, Sabrina; Carton, Xavier; Blanke, Bruno
Abstract: The turbulent processes in the Cape Basin, the southeasternmost gate of the Atlantic Ocean, play a key role in the transport and mixing of upper to intermediate water masses entering the area from the Indian Ocean, making them especially relevant for the Indo‐Atlantic transfer of heat and salt. In this paper, two numerical simulations at different horizontal resolutions are used to study mesoscale and submesoscale dynamics, their phenomenology, their evolution, and their impact on the local water masses. Submesoscale processes seasonally affect both, the upper and intermediate layers, but there are clear dynamical differences between the two layers. Several types of instabilities underline this spatial and temporal variability. Near the surface, mixed layer instabilities occur during winter, while mesoscale‐driven instabilities, as the symmetric type, prevail in summer. The connection between these two seasonal regimes is ensured, in anticyclonic eddies and within the mixed layers, by Charney baroclinic instabilities, involved in the local formation and subduction of mode water, that we have dubbed as Agulhas Rings mode water. Intermediate depths are instead characterized by mesoscale mechanisms of density compensation and lateral stirring of the tracer variance, triggering a significant filamentogenesis whose vertical scales are comparable to those mentioned in previous studies. This leads to a particularly efficient mixing of Antarctic Intermediate Waters of Indian and Atlantic origins. Lagrangian estimates highlight the new and significant role of fine scale structures in setting the water masses properties of upper and lower thermocline waters materializing the Indo‐Atlantic exchange and therefore potentially affecting the global ocean circulation. Key Points: Mesoscale spatiotemporal variability in the Cape Basin is also influenced by submesoscale mechanisms Seasonality of the flow instabilities highly affects the dynamics of the upper and lower thermocline water masses Small‐scale processes strongly impacts the Indo‐Atlantic transports of heat and salt